2022
DOI: 10.1038/s41598-022-12747-8
|View full text |Cite
|
Sign up to set email alerts
|

Boosting SARS-CoV-2 detection combining pooling and multiplex strategies

Abstract: RT-qPCR is the gold standard technique available for SARS-CoV-2 detection. However, the long test run time and costs associated with this type of molecular testing are a challenge in a pandemic scenario. Due to high testing demand, especially for monitoring highly vaccinated populations facing the emergence of new SARS-CoV-2 variants, strategies that allow the increase in testing capacity and cost savings are needed. We evaluated a RT-qPCR pooling strategy either as a simplex and multiplex assay, as well as pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The cost of Dorfman-based pool testing was calculated from one large-scale real-practice screening. 18 The model showed that the cost-effectiveness of FLIPNAS is comparable with that of Dorfman group testing at a low prevalence, such as 1%. The Dorfman-based group testing (ESI Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The cost of Dorfman-based pool testing was calculated from one large-scale real-practice screening. 18 The model showed that the cost-effectiveness of FLIPNAS is comparable with that of Dorfman group testing at a low prevalence, such as 1%. The Dorfman-based group testing (ESI Fig.…”
Section: Resultsmentioning
confidence: 92%
“…To assess the economy of FLIPNAS, we calculated the hypothetical cost savings with a similar prevalence of around 7% found in one practical large-scale screening. 18 We found that utilizing FLIPNAS would represent savings of 86.97% and 73.37% compared with individual PCR tests and the Dorfman group testing, respectively (ESI Table S6 †). These savings were attributed to the removal of the retesting step for positive pools, the further enlarged pool size, and as there is no requirement for expensive probe modification.…”
Section: Validation With Clinical Samples and Assessing The Economy O...mentioning
confidence: 89%
See 1 more Smart Citation
“…One such solution, in which these factors are fed to an AI algorithm, has already been developed and successfully implemented by us to support the mass testing program in companies of the state of Rio de Janeiro, increasing the throughput and reducing costs. A straight-forward add-on was the pooling of asymptomatic samples, with individual re-testing restricted to positive pools ( 19 , 20 ). Here, statistical modeling predicted a cost saving of 48% when prevalence rates reach around 7.5% and a four-samples pooling strategy is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Here, statistical modeling predicted a cost saving of 48% when prevalence rates reach around 7.5% and a four-samples pooling strategy is adopted. Indeed, in our mass-testing routine, this strategy accounts for a cost saving of about 51%, already considering subsequent re-testing of individual samples and false-negative rates ( 20 ).…”
Section: Discussionmentioning
confidence: 99%